The Effective Utilization of Knowledge Management in E-Government: A Case Study of E-Government in Jordan - Amyan, Mozfi Mohammad; Al-saudi, Musa; Al-Onizat, Hamdan Hasan (European Scientific Journal, ESJ, 2016)
The study is aimed at investigating the effective utilization of knowledge management in the Jordanian e-government system. The study proposes the knowledge management model for the implementation of egovernment in Jordan. The sample consisted of 132 employees derived from a population that had a sufficient knowledge of knowledge management in the Jordanian e-government team. The data collection tool used was a selfadministrated questionnaire. The study revealed the existence of a strong correlation between knowledge management and the utilization of knowledge. Furthermore, the study sample agreed that knowledge management is a widespread organizational practice. The study concluded that the utilization of knowledge is related to proper planning and follow-up of the applications for the knowledge management in Jordan e-government entities. In addition, the study recommended the spread of the culture of knowledge management which was supported by the senior management at the Jordanian entities.